Preparation method and application of N / P / S multi-element doped in-situ growth carbon nanotube composite positive electrode material

By preparing N/P/S multi-element doped in situ growing carbon nanotube composite cathode material, the problems of unstable structure and poor cycle stability of lithium-sulfur batteries are solved, and higher electrode stability and performance are achieved.

CN119480984AActive Publication Date: 2025-02-18CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411606171.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The positive electrode structure of lithium-sulfur batteries is unstable and the cycle stability is poor.

Method used

The preparation method of using N/P/S multi-element doped in situ growing carbon nanotube composite cathode material, including extracting lecithin, preparing sulfur-nitrogen double-doped carbon nitride, preparing plastic solids, and preparing N/P/S Multi-element doped composite carbon materials, preparation of precursors and finally incorporating sulfur into the carbon materials by melting.

Benefits of technology

The structural stability and cyclic stability of the positive electrode of the lithium sulfur battery are improved, the stability of the specific capacitor under high current density is ensured, and the capacity and cyclic performance of the electrode are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480984A_ABST
    Figure CN119480984A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrode material preparation, in particular to a preparation method and application of an N / P / S multi-element doped in-situ growth carbon nanotube composite positive electrode material, and the preparation method comprises the following steps: extracting lecithin; preparing sulfur and nitrogen double-doped carbon nitride; preparing a plastic-like solid; preparing an N / P / S multi-element doped composite carbon material; preparing a precursor; preparing an N / P / S multi-element doped in-situ growth carbon nanotube composite carbon material; and preparing the N / P / S multi-element doped in-situ growth carbon nanotube composite positive electrode material. The N / P / S multi-element doped in-situ growth carbon nanotube composite positive electrode prepared by the method can ensure the stability of specific capacitance under high current density. Besides, the N / P / S multi-element doped in-situ growth carbon nanotube composite positive electrode prepared based on the method contains abundant micropores and carbon nanotube structures, so that the prepared electrode is stable in structure and has relatively high capacity and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrode material preparation, and in particular to a preparation method and application of an N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material. Background Art

[0002] Lithium-sulfur battery is an energy storage system consisting of a sulfur (S) composite positive electrode, a metal lithium (Li) negative electrode and an electrolyte between the two. Lithium-sulfur battery is considered to be a very promising new secondary battery system due to its high energy density (2600Whkg-1), wide operating temperature (-30~60℃) and low electrode material cost. However, in the related technology, the positive electrode of lithium-sulfur battery is usually made of composite materials, and the obtained positive electrode has unstable structure and poor cycle stability. Summary of the invention

[0003] The present application provides a preparation method and application of an N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material to solve the problems of instability of the positive electrode structure and poor cycle stability of lithium-sulfur batteries in the related art.

[0004] In order to achieve the above objectives, in a first aspect, the present application provides a method for preparing a N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material, comprising the following steps:

[0005] Extract lecithin: Use ethanol solution as solvent to dissolve egg yolk, and extract lecithin in a water bath;

[0006] Preparation of sulfur-nitrogen dual-doped carbon nitride: urea and thiourea are mixed in a mass ratio of 1:1, ground, and then placed in a muffle furnace for calcination to obtain sulfur-nitrogen dual-doped carbon nitride;

[0007] Preparation of a plastic-like solid: dissolving lecithin and sulfur-nitrogen co-doped carbon nitride in an ethanol solution at a mass ratio of 8:10, and then sonicating and subjecting the mixture to a water bath until the ethanol is evaporated to dryness to obtain a plastic-like solid;

[0008] Preparation of N / P / S multi-element doped composite carbon material: placing a plastic-like solid on a magnetic boat and placing it in a tube furnace, and calcining it under an inert atmosphere to obtain a N / P / S multi-element doped composite carbon material;

[0009] Preparing a precursor: dissolving the N / P / S multi-element doped composite carbon material, melamine and cobalt nitrate hexahydrate in a mass ratio of 8:2 in an ethanol solution, and then performing ultrasonication and water bathing until the ethanol is evaporated to dryness to obtain a precursor;

[0010] Preparation of N / P / S multi-element doped in-situ grown carbon nanotube composite carbon material: placing the precursor on a magnetic boat and placing it in a tube furnace, and calcining it under an inert atmosphere to obtain N / P / S multi-element doped in-situ grown carbon nanotube composite carbon material;

[0011] Preparation of N / P / S multi-element doped in situ grown carbon nanotube composite positive electrode material: sulfur is doped into the carbon body of N / P / S multi-element doped in situ grown carbon nanotube composite carbon material by a melting method, and the mass ratio of sulfur to carbon body is 7:3, to obtain N / P / S multi-element doped in situ grown carbon nanotube composite positive electrode material.

[0012] In some embodiments of the present application, in the step of extracting lecithin,

[0013] Add ethanol in 3 to 4 times, each time adding ethanol solution 2 to 4 times the volume of egg yolk to dissolve, separate the supernatant, and evaporate the ethanol in a 100°C water bath for 1 to 3 hours to obtain lecithin;

[0014] The volume ratio of ethanol to water in the ethanol solution is 0.5-4.

[0015] In some embodiments of the present application, in the step of preparing sulfur-nitrogen dual-doped carbon nitride,

[0016] The grinding time is 1 to 3 hours; the heating rate of roasting is 1 to 10°C / min, the roasting temperature is 500 to 1800°C, and the roasting time is 0.5 to 8 hours.

[0017] In some embodiments of the present application, in the step of preparing a plastic-like solid,

[0018] The ethanol solution is 20-50 ml, the ultrasonic grinding time is 20-30 min, the water bath temperature is 60-100° C., and the water bath time is 2-4 h.

[0019] In some embodiments of the present application, in the step of preparing the N / P / S multi-element doped composite carbon material,

[0020] The inert gas under the inert atmosphere is nitrogen or argon, and the inert gas flow rate is 20 to 300 mL / min; the heating rate of the roasting is 1 to 10° C. / min, the roasting temperature is 500 to 1200° C., and the roasting time is 0.5 to 3 h.

[0021] In some embodiments of the present application, in the step of preparing a precursor,

[0022] The N / P / S multi-element doped composite carbon material is 0.01-0.03g, the melamine is 6-8g; the cobalt nitrate hexahydrate is 1.5-2g, and the ethanol solution is 20-50ml;

[0023] The ultrasonic time is 20 to 30 minutes, the water bath temperature is 60 to 80°C, and the water bath time is 6 to 8 hours.

[0024] In some embodiments of the present application, in the step of preparing the N / P / S multi-element doped in-situ grown carbon nanotube composite carbon material,

[0025] The inert gas under the inert atmosphere is nitrogen or argon, and the inert gas flow rate is 20 to 300 mL / min;

[0026] The roasting includes a first roasting and a second roasting which are carried out in sequence. The heating rate of the first roasting is 1-10°C / min, the roasting temperature is 400-600°C, and the roasting time is 0.5-3h; the heating rate of the second roasting is 1-10°C / min, the roasting temperature is 700-1100°C, and the roasting time is 0.5-3h.

[0027] In some embodiments of the present application, in the step of preparing the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material,

[0028] The reaction temperature of the melt method is 155°C and the reaction time is 12 to 24 hours.

[0029] In the second aspect, an application of the composite positive electrode material obtained according to the aforementioned preparation method in preparing a positive electrode for a lithium-sulfur battery is specifically:

[0030] The N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material, the conductive material and the binder are uniformly mixed in a mass ratio of 7 to 9.5:1:1 to obtain a coating material, wherein the conductive material is conductive carbon and the binder is polyvinylidene fluoride;

[0031] The coating material is coated on the carrier, dried and sliced ​​to obtain the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode sheet, wherein the carrier is aluminum foil, the drying temperature is 40-150° C., and the drying time is 2-36 hours.

[0032] The present application provides a preparation method and application of an N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material. Lecithin can be extracted from egg yolk, and the raw material is cheap and easily available. Lecithin itself has multiple elements such as N / O / P / S, and its element content is rich. The carbon nitride prepared from urea and the carbon nitride prepared from thiourea participate in the preparation of carbon materials to increase the crystallinity and graphitization degree. N, P, S co-doping, porous structure and carbon nanotubes have a strong adsorption effect on soluble polysulfides, so that it has good stability and rate performance. The N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode prepared by the above method can ensure the stability of specific capacitance even under high current density.

[0033] In addition, the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode prepared based on the above method contains abundant micropores and carbon nanotube structures, so that the prepared electrode structure is stable and has high capacity and cycle performance.

[0034] The structure of the present application and its other application objects and beneficial effects will be more clearly understood through the description of the preferred embodiments in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0036] Figure 1 This is the SEM image of the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material of this application.

[0037] Figure 2 This is a partially enlarged view of the SEM image of the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material of the present application.

[0038] Figure 3 This is a mapping image of the nitrogen element in a partially enlarged view of the SEM image of the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material of the present application.

[0039] Figure 4 This is a mapping image of the phosphorus element in a partially enlarged view of the SEM image of the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material of the present application.

[0040] Figure 5 This is a mapping image of the sulfur element in a partially enlarged view of the SEM image of the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material of the present application.

[0041] Figure 6 This is a mapping image of the carbon element in a partially enlarged view of the SEM image of the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material of the present application.

[0042] Figure 7 This is a mapping image of the cobalt element in a partially enlarged view of the SEM image of the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material of the present application.

[0043] Figure 8 This is the cyclic charge-discharge curve of the N / P / S multi-element doped in-situ grown carbon nanotube composite electrode of this application.

[0044] The above drawings have shown clear embodiments of the present application, which will be described in more detail later. These drawings and text descriptions are not intended to limit the scope of the present application in any way, but to illustrate the concept of the present application to those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme in the embodiment of the present application will be described in more detail below in conjunction with the drawings in the preferred embodiments of the present application. In the drawings, the same or similar reference numerals throughout represent the same or similar parts or parts with the same or similar functions. The described embodiments are part of the embodiments of the present application, not all of the embodiments. The embodiments described below with reference to the drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limitations on the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application. The embodiments of the present application are described in detail below in conjunction with the drawings.

[0046] In a first aspect, the present application provides a method for preparing a N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material, comprising the following steps:

[0047] Extract lecithin: Use ethanol solution as solvent to dissolve egg yolk, and extract lecithin in a water bath;

[0048] Preparation of sulfur-nitrogen dual-doped carbon nitride: urea and thiourea are mixed in a mass ratio of 1:1, ground, and then placed in a muffle furnace for calcination to obtain sulfur-nitrogen dual-doped carbon nitride;

[0049] Preparation of a plastic-like solid: dissolving lecithin and sulfur-nitrogen co-doped carbon nitride in an ethanol solution at a mass ratio of 8:10, and then sonicating and subjecting the mixture to a water bath until the ethanol is evaporated to dryness to obtain a plastic-like solid;

[0050] Preparation of N / P / S multi-element doped composite carbon material: placing a plastic-like solid on a magnetic boat and placing it in a tube furnace, and calcining it under an inert atmosphere to obtain a N / P / S multi-element doped composite carbon material;

[0051] Preparing a precursor: dissolving the N / P / S multi-element doped composite carbon material, melamine and cobalt nitrate hexahydrate in a mass ratio of 8:2 in an ethanol solution, and then performing ultrasonication and water bathing until the ethanol is evaporated to dryness to obtain a precursor;

[0052] Preparation of N / P / S multi-element doped in-situ grown carbon nanotube composite carbon material: placing the precursor on a magnetic boat and placing it in a tube furnace, and calcining it under an inert atmosphere to obtain N / P / S multi-element doped in-situ grown carbon nanotube composite carbon material;

[0053] Preparation of N / P / S multi-element doped in situ grown carbon nanotube composite positive electrode material: sulfur is doped into the carbon body of N / P / S multi-element doped in situ grown carbon nanotube composite carbon material by a melting method, and the mass ratio of sulfur to carbon body is 7:3, to obtain N / P / S multi-element doped in situ grown carbon nanotube composite positive electrode material.

[0054] It should be noted that the melting method is simple and easy to operate, has low cost, and can diffuse sulfur into the interior of the material.

[0055] In some embodiments of the present application, in the step of extracting lecithin,

[0056] Add ethanol in 3 to 4 times, each time adding ethanol solution 2 to 4 times the volume of egg yolk to dissolve, separate the supernatant, and evaporate the ethanol in a 100°C water bath for 1 to 3 hours to obtain lecithin;

[0057] The volume ratio of ethanol to water in the ethanol solution is 0.5-4.

[0058] In some embodiments of the present application, in the step of preparing sulfur-nitrogen dual-doped carbon nitride,

[0059] The grinding time is 1 to 3 hours; the heating rate of roasting is 1 to 10°C / min, the roasting temperature is 500 to 1800°C, and the roasting time is 0.5 to 8 hours.

[0060] In some embodiments of the present application, in the step of preparing a plastic-like solid,

[0061] The ethanol solution is 20-50 ml, the ultrasonic grinding time is 20-30 min, the water bath temperature is 60-100° C., and the water bath time is 2-4 h.

[0062] In some embodiments of the present application, in the step of preparing the N / P / S multi-element doped composite carbon material,

[0063] The inert gas under the inert atmosphere is nitrogen or argon, and the inert gas flow rate is 20 to 300 mL / min; the heating rate of the roasting is 1 to 10° C. / min, the roasting temperature is 500 to 1200° C., and the roasting time is 0.5 to 3 h.

[0064] In some embodiments of the present application, in the step of preparing a precursor,

[0065] The N / P / S multi-element doped composite carbon material is 0.01-0.03g, the melamine is 6-8g; the cobalt nitrate hexahydrate is 1.5-2g, and the ethanol solution is 20-50ml;

[0066] The ultrasonic time is 20 to 30 minutes, the water bath temperature is 60 to 80°C, and the water bath time is 6 to 8 hours.

[0067] In some embodiments of the present application, in the step of preparing the N / P / S multi-element doped in-situ grown carbon nanotube composite carbon material,

[0068] The inert gas under the inert atmosphere is nitrogen or argon, and the inert gas flow rate is 20 to 300 mL / min;

[0069] The roasting includes a first roasting and a second roasting which are carried out in sequence. The heating rate of the first roasting is 1-10°C / min, the roasting temperature is 400-600°C, and the roasting time is 0.5-3h; the heating rate of the second roasting is 1-10°C / min, the roasting temperature is 700-1100°C, and the roasting time is 0.5-3h.

[0070] In some embodiments of the present application, in the step of preparing the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material,

[0071] The reaction temperature of the melt method is 155°C and the reaction time is 12 to 24 hours.

[0072] In the second aspect, an application of the composite positive electrode material obtained according to the aforementioned preparation method in preparing a positive electrode for a lithium-sulfur battery is specifically:

[0073] The N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material, the conductive material and the binder are uniformly mixed in a mass ratio of 7 to 9.5:1:1 to obtain a coating material, wherein the conductive material is conductive carbon; the binder is polyvinylidene fluoride;

[0074] The coating material is coated on the carrier, dried and sliced ​​to obtain the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode sheet, wherein the carrier is aluminum foil, the drying temperature is 40-150° C., and the drying time is 2-36 hours.

[0075] The present application provides a preparation method and application of an N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material. Lecithin can be extracted from egg yolk, and the raw material is cheap and easily available. Lecithin itself has multiple elements such as N / O / P / S, and its element content is rich. The carbon nitride prepared from urea and the carbon nitride prepared from thiourea participate in the preparation of carbon materials to increase the crystallinity and graphitization degree. N, P, S co-doping, porous structure and carbon nanotubes have a strong adsorption effect on soluble polysulfides, so that it has good stability and rate performance. The N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode prepared by the above method can ensure the stability of specific capacitance even under high current density.

[0076] In addition, the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode prepared based on the above method contains abundant micropores and carbon nanotube structures, so that the prepared electrode structure is stable and has high capacity and cycle performance.

[0077] The preparation method of the multi-element doped in-situ grown carbon nanotube composite material of the present application will be described in detail below with reference to specific embodiments.

[0078] Embodiment 1

[0079] A method for preparing a N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material comprises the following steps:

[0080] The quail yellow was dissolved in ethanol by using ethanol as solvent. Specifically, ethanol was added in 3 times, and each time, ethanol solution of 2 times the volume of the quail yellow was added for dissolution. The supernatant was extracted and separated. The ethanol was evaporated in a 100° C. water bath for 1 h to obtain lecithin.

[0081] 10 g of thiourea and 10 g of urea were mixed and ground for 3 h, then placed in a crucible and calcined at 550 ° C in a muffle furnace for 1 h to obtain sulfur-nitrogen dual-doped carbon nitride (SNg-C3N4). It should be noted that the order of mixing and grinding is not limited, that is, mixing can be performed first and then grinding, or grinding can be performed first and then mixing.

[0082] 0.8 g of lecithin, 1 g of sulfur-nitrogen dual-doped carbon nitride (SNg-C3N4) and 20 mL of ethanol solution were mixed and ultrasonically treated for 20 min. The ethanol was evaporated in a water bath at 80°C for 2 h to obtain a plastic-like solid.

[0083] The plastic-like solid is transferred to a corundum magnetic boat, placed in a tubular furnace, a heating program is set, and high-purity argon gas is introduced to purge the air in the furnace tube. The inert gas flow rate is 20 mL / min and the ventilation time is 1 h. Then, heating is carried out, and the heating program is increased to 1000 °C at a heating rate of 5 °C / min and maintained at a constant temperature for 2 h to obtain N / P / S multi-element doped composite carbon material (NPSC).

[0084] 0.01 g of N / P / S multi-element doped composite carbon material (NPSC), 8 g of melamine and 2 g of cobalt nitrate hexahydrate were dissolved in 20 mL of ethanol solution, ultrasonically treated for 20 min, and the ethanol was evaporated in a water bath at 80° C. for 8 h to obtain a precursor.

[0085] Collect the precursor, transfer it to a corundum crucible, place it in a tube furnace, set the temperature program, and introduce high-purity argon to purge the air in the furnace tube. The inert gas flow rate is 20mL / min, and the ventilation time is 1h. Then heat it up, and the temperature program is to increase the temperature to 500℃ at a heating rate of 5℃ / min and keep it at a constant temperature for 2h; then increase the temperature to 700℃ at a heating rate of 5℃ / min and keep it at a constant temperature for 2h, and then continue to pass argon until the temperature of the furnace tube naturally cools to room temperature.

[0086] Sulfur is doped into the carbon main body of the N / P / S multi-element doped in-situ grown carbon nanotube composite carbon material by a melting method, the mass ratio of sulfur to the carbon main body is 7:3, and the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material is obtained.

[0087] Electrode fabrication:

[0088] The prepared composite positive electrode material, conductive material and binder are mixed in a ratio of 8:1:1 (mass ratio), N-methylpyrrolidone (NMP) is added as a solvent, and the mixture is ground evenly to obtain a slurry, wherein the conductive material is conductive carbon (Super P) and the binder is polyvinylidene fluoride.

[0089] A 20 cm×20 cm carbon-coated aluminum foil was used as a current collector, and the slurry was evenly coated on the current collector. Subsequently, the current collector was placed in a vacuum drying oven and dried at 40° C. for 24 h for later use.

[0090] A disc with a diameter of 12 mm was punched out using a punching machine as the positive electrode sheet, and its mass was weighed to calculate the sulfur loading per unit area.

[0091] Button battery assembly:

[0092] Assemble into CR2025 button cells for subsequent charge and discharge tests. Since both Li and electrolyte in Li-S batteries are sensitive to air and water, battery assembly needs to be carried out in a glove box. The negative electrode is metallic Li, the separator is Celgard2400, and the electrolyte dosage is about 15μL mg -1 The composition is 1 M LiTFSI dissolved in a binary solvent of 1,2-dimethoxyethane and 1,3-dioxolane in a volume ratio of 1:1, and the additive is 2wt% lithium nitrate.

[0093] Electrochemical performance test:

[0094] The electrode prepared in the example was subjected to an electrode performance test.

[0095] Constant current charge and discharge test: This application uses a battery testing system to perform rate performance tests on assembled batteries. During the test, the battery needs to be activated twice at a current density of 0.1C. The voltage range during the cycle and rate tests is 1.7-2.8V, the current density during the cycle test is 0.5C, and the current density during the rate test is 0.2C, 0.5C, 1C, 2C, and then back to 0.5C, 0.2C.

[0096] The final product is a composite material of carbon nanotubes encapsulated by metallic Co and embedded in N, P, and S co-doped carbon foam. Figure 1 This is the SEM image of the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material of this application. Figure 1 It can be seen that this material has unique structural characteristics: Co nanoparticles are encapsulated in three-dimensional porous N, P, S-doped foam carbon interconnected with carbon nanotube (CNT) branches. By encapsulating Co nanoparticles, introducing N, P, S elements co-doping and constructing a three-dimensional porous structure composed of bamboo-like CNT branches, the N, P, S co-doped structure significantly accelerates the transmission of electrons and effectively limits the diffusion of polysulfides. Figure 2 This is a partially enlarged view of the SEM image of the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material of the present application.

[0097] Figure 3 This is a mapping image of nitrogen in a local magnified image of the SEM image of the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material of this application. Figure 3 It can be seen that the nitrogen element is evenly distributed. Figure 4 This is a mapping image of phosphorus in a local magnified image of the SEM image of the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material of this application. Figure 4 It can be seen that phosphorus is evenly distributed. Figure 5 This is a mapping image of sulfur element in a partial magnified image of the SEM image of the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material of this application. Figure 5 It can be seen that the sulfur element is evenly distributed. Figure 6 This is a mapping image of carbon elements in a partial magnified image of the SEM image of the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material of this application. Figure 6 It can be seen that the carbon element is evenly distributed. Figure 7 This is a mapping image of the cobalt element in a local enlarged view of the SEM image of the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material of this application. Figure 7 It can be seen that the cobalt element is evenly distributed. Figure 8 This is the cyclic charge-discharge curve of the N / P / S multi-element doped in-situ grown carbon nanotube composite electrode in this application. Figure 8 It can be seen that the positive electrode material of the composite material loaded with sulfur shows 1215.43 mAh g under 0.2C conditions. -1 High specific capacity, maintaining 802.13 mAh g at 2C -1 It has a capacity of 2.5W and can still maintain a high specific capacity and stability under high rate and long cycle conditions, showing obvious advantages in electrochemical performance.

[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material, characterized in that: The steps include: Extract lecithin: Use ethanol solution as solvent to dissolve egg yolk, and extract lecithin in a water bath; Preparation of sulfur-nitrogen dual-doped carbon nitride: urea and thiourea are mixed in a mass ratio of 1:1, ground, and then placed in a muffle furnace for calcination to obtain sulfur-nitrogen dual-doped carbon nitride; Preparation of a plastic-like solid: dissolving lecithin and sulfur-nitrogen co-doped carbon nitride in an ethanol solution at a mass ratio of 8:10, and then sonicating and subjecting the mixture to a water bath until the ethanol is evaporated to dryness to obtain a plastic-like solid; Preparation of N / P / S multi-element doped composite carbon material: placing a plastic-like solid on a magnetic boat and placing it in a tube furnace, and calcining it under an inert atmosphere to obtain a N / P / S multi-element doped composite carbon material; Preparing a precursor: dissolving the N / P / S multi-element doped composite carbon material, melamine and cobalt nitrate hexahydrate in a mass ratio of 8:2 in an ethanol solution, and then performing ultrasonication and water bathing until the ethanol is evaporated to dryness to obtain a precursor; Preparation of N / P / S multi-element doped in-situ grown carbon nanotube composite carbon material: placing the precursor on a magnetic boat and placing it in a tube furnace, and calcining it under an inert atmosphere to obtain N / P / S multi-element doped in-situ grown carbon nanotube composite carbon material; Preparation of N / P / S multi-element doped in situ grown carbon nanotube composite positive electrode material: sulfur is doped into the carbon body of N / P / S multi-element doped in situ grown carbon nanotube composite carbon material by a melting method, and the mass ratio of sulfur to carbon body is 7:3, to obtain N / P / S multi-element doped in situ grown carbon nanotube composite positive electrode material.

2. The method for preparing the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material according to claim 1, characterized in that: In the step of extracting lecithin, Add ethanol in 3 to 4 times, each time adding ethanol solution 2 to 4 times the volume of egg yolk to dissolve, separate the supernatant, and evaporate the ethanol in a 100°C water bath for 1 to 3 hours to obtain lecithin; The volume ratio of ethanol to water in the ethanol solution is 0.5-4.

3. The method for preparing the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material according to claim 1, characterized in that: In the step of preparing sulfur-nitrogen dual-doped carbon nitride, The grinding time is 1 to 3 hours; the heating rate of roasting is 1 to 10°C / min, the roasting temperature is 500 to 1800°C, and the roasting time is 0.5 to 8 hours.

4. The method for preparing the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material according to claim 1, characterized in that: In the step of preparing a plastic-like solid, The ethanol solution is 20-50 ml, the ultrasonic time is 20-30 min, the water bath temperature is 60-100°C, and the water bath time is 2-4 h.

5. The method for preparing the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material according to claim 1, characterized in that: In the step of preparing the N / P / S multi-element doped composite carbon material, The inert gas under the inert atmosphere is nitrogen or argon, and the inert gas flow rate is 20 to 300 mL / min; the heating rate of the roasting is 1 to 10° C. / min, the roasting temperature is 500 to 1200° C., and the roasting time is 0.5 to 3 h.

6. The method for preparing the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material according to claim 1, characterized in that: In the step of preparing the precursor, The N / P / S multi-element doped composite carbon material is 0.01-0.03g, the melamine is 6-8g; the cobalt nitrate hexahydrate is 1.5-2g, and the ethanol solution is 20-50ml; The ultrasonic time is 20 to 30 minutes, the water bath temperature is 60 to 80°C, and the water bath time is 6 to 8 hours.

7. The method for preparing the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material according to claim 1, characterized in that: In the step of preparing the N / P / S multi-element doped in-situ grown carbon nanotube composite carbon material, The inert gas under the inert atmosphere is nitrogen or argon, and the inert gas flow rate is 20 to 300 mL / min; The roasting includes a first roasting and a second roasting which are carried out in sequence. The heating rate of the first roasting is 1-10°C / min, the roasting temperature is 400-600°C, and the roasting time is 0.5-3h; the heating rate of the second roasting is 1-10°C / min, the roasting temperature is 700-1100°C, and the roasting time is 0.5-3h.

8. The method for preparing the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material according to claim 1, characterized in that: In the step of preparing the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material, The reaction temperature of the melt method is 155°C and the reaction time is 12 to 24 hours.

9. An application of the composite positive electrode material obtained by the preparation method according to any one of claims 1 to 8 in preparing a positive electrode for a lithium-sulfur battery, characterized in that: The N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode material, the conductive material and the binder are uniformly mixed in a mass ratio of 7 to 9.5:1:1 to obtain a coating material, wherein the conductive material is conductive carbon and the binder is polyvinylidene fluoride; The coating material is coated on the carrier, dried and sliced ​​to obtain the N / P / S multi-element doped in-situ grown carbon nanotube composite positive electrode sheet, wherein the carrier is aluminum foil, the drying temperature is 40-150° C., and the drying time is 2-36 hours.

Citation Information

Patent Citations

  • Photocatalyst composite structure and preparation method thereof

    CN104801325A

  • Method for synthesis of cobalt nanoparticle and bamboo-like nitrogen doped carbon nanotube composite material

    CN104944410A

  • Synthesis of highly nitrogen doped carbon nanostructures

    IN201641029179A